Dampak Sosial Ekonomi Pertambangan Terhadap Masyarakat di Desa Kubung Kecamatan Bacan Selatan Kabupaten Halmahera Selatan - Hadi, Samsul; Djimar, Sartini; Mane, Hikmawati Ode (Jurnal Ilmiah Wahana Pendidikan, 2025)
Mining has a significant impact on the social and economic aspects of communities, especially in areas that rely on natural resources. This study aims to analyze the social and economic impacts of mining activities on the community in Kubung Village, Bacan Selatan District, South Halmahera Regency, based on the latest literature review. The findings indicate that the mining sector provides economic benefits such as increased income and job opportunities but also leads to high economic dependence on the industry. On the other hand, social impacts include changes in lifestyle, social conflicts, economic disparities, and health risks due to environmental pollution. Additionally, the presence of mining operations raises the cost of living due to the surge in prices of goods and services. Therefore, stricter policies are needed in mining regulations, community empowerment through livelihood diversification, and sustainable reclamation and environmental restoration programs. This study highlights the importance of balancing resource exploitation with community welfare to ensure long-term benefits for local residents.